2023
DOI: 10.1002/adfm.202211801
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Pressure Regimes in Anisotropically Strained V2O3 Films

Abstract: The metal-insulator phase transitions in V 2 O 3 are considered archetypal manifestations of Mott physics. Despite decades of research, the effects of doping, pressure, and anisotropic strains on the transitions are still debated. To understand how these parameters control the transitions, anisotropically strained pure V 2 O 3 films are explored with nearly the same contraction along the c-axis, but different degrees of ab-plane expansion. With small ab-plane expansion, the films behave similar to bulk V 2 O 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…On the other hand, for the sample with c / a = 2.82 bent along CO [210], the increase in the T MIT is only ∼5 K under ε b = +0.25%, while the decrease is as high as ∼24 K under ε b = −0.25%. Previous reports indicated that V 2 O 3 exhibits an intricate lattice strain dependence of MIT characteristics due to the strong interplay among multiple DOF. ,, Herein, the substantial and anisotropic dependence of Δ T MIT on ε b further highlights the great potential for application and extensive fundamental physics in the V 2 O 3 material system.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, for the sample with c / a = 2.82 bent along CO [210], the increase in the T MIT is only ∼5 K under ε b = +0.25%, while the decrease is as high as ∼24 K under ε b = −0.25%. Previous reports indicated that V 2 O 3 exhibits an intricate lattice strain dependence of MIT characteristics due to the strong interplay among multiple DOF. ,, Herein, the substantial and anisotropic dependence of Δ T MIT on ε b further highlights the great potential for application and extensive fundamental physics in the V 2 O 3 material system.…”
Section: Resultsmentioning
confidence: 99%
“…48 Previous investigations have shown that factors such as doping, defects, offstoichiometry, hydrostatic pressure, and strain are influential in determining the MIT behavior of V 2 O 3 films. 11,14,18,19,49 Although there are numerous factors to consider, the c/a ratio is commonly utilized as an indicator that is closely linked to MIT behavior. 12,18,45 Considering that the use of different growth conditions inevitably leads to distortions, defects, and off-stoichiometry, the various ρ vs T curves in our samples grown under different conditions could be due to the potential existence of nonstoichiometric V 2−y O 3 phases.…”
Section: Structural Characterizationmentioning
confidence: 99%
See 3 more Smart Citations